Pengaruh Perceived Value dan Brand Credibility terhadap Purchase Intention dengan Moderasi Fear of Missing Out (FOMO) - Siti Julaeha; Rojuaniah Rojuaniah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid development of the fashion industry in the digital era has increased competition for local fashion brands in attracting consumer purchase intention, especially Generation Z which is strongly influenced by trends and social media. This study aims to analyze the effect of perceived value, brand credibility, Fear of missing out (FoMO), on purchase intention, and test the moderating role of FoMO in the relationship between brand credibility and purchase intention. The study used a quantitative approach with a survey method on the population of Generation Z female consumers aged 18-28 years who live in the Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) areas with a sample of 160 respondents through purposive sampling technique. Data analysis was conducted using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results showed that perceived value, brand credibility, and FoMO have a positive and significant effect on purchase intention. In addition, FoMO is proven to be able to strengthen the relationship between brand credibility and purchase intention. This research provides implications for fashion industry players to increase perceived value, strengthen brand credibility, and utilize relevant digital strategies to encourage consumer purchase intention.